2007
DOI: 10.2114/jpa2.26.69
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Visual Display Terminal Use on the Physical and Mental Conditions of Administrative Staff in Japan

Abstract: Visual display terminals (VDT) are standard equipment for many office workers. Their use, however, may increase the risk of developing adverse conditions related to vision, the musculoskeletal system, and mental health. We carried out a survey among 3070 workers aged 18 to 67 years (mean, 39.9 years) at a prefectural administrative office, in which 76% of subjects were visual display terminal (VDT) users. We examined the relationship between duration of daily VDT use and eyestrain, neck or upper extremity pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 21 publications
3
46
1
2
Order By: Relevance
“…A positive association between musculoskeletal symptoms and duration of computer use has been shown in earlier studies (Demure et al 2000;Jensen et al 2002;Blatter and Bongers 2002;Karlqvist et al 2002;Juul-Kristensen and Jensen 2005;Ye et al 2007). However, differences in selection criteria for the study populations, assessment of outcome measures and categorisation of Although it has been shown that self-reported durations of computer activities are not always accurate if compared to objectively obtained data, the inaccuracy concerned an overestimate of computer activity by self-reporting (Heinrich et al 2004;Mikkelsen et al 2007).…”
Section: Discussionsupporting
confidence: 57%
“…A positive association between musculoskeletal symptoms and duration of computer use has been shown in earlier studies (Demure et al 2000;Jensen et al 2002;Blatter and Bongers 2002;Karlqvist et al 2002;Juul-Kristensen and Jensen 2005;Ye et al 2007). However, differences in selection criteria for the study populations, assessment of outcome measures and categorisation of Although it has been shown that self-reported durations of computer activities are not always accurate if compared to objectively obtained data, the inaccuracy concerned an overestimate of computer activity by self-reporting (Heinrich et al 2004;Mikkelsen et al 2007).…”
Section: Discussionsupporting
confidence: 57%
“…In one Notes. x 1 -mean value in workers with health complaints, x 2 -mean value in workers without health complaints (control group), OR-odds ratio, CI-confidence interval, BMI-body mass index (kilograms/metre large Indian study, 46.3% of computer operators were affected by astenophy [9], while in Italy this number was 63.1% [10] and in Japan only 17% of computer operators reported visual disturbs [11]. Mental complaints with the prevalence of 7.1% were the third most frequent health disorder in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the percentage of workers with mental health problems (i.e., strong anxiety, distress and stress) in a recent study conducted in Japan was found to be approximately 60%, which was attributed to rapid generalization of VDT use in the workplace (17). Ye et al identified that >5 h of VDT use at work each day was significantly associated with deterioration of mental health status and concluded that prolonged usage of a VDT for work-related tasks is a risk factor for mental disorders (18). In addition, companies in the information and communication industry in Japan showed the highest percentage (28.5%) of employees who were absent from work for more than 1 month due to a mental health problem (17).…”
Section: Association Of Temporomandibular Disorder With Occupational mentioning
confidence: 99%